2012
DOI: 10.1073/pnas.1216039110
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and self-assembly in the control of a bacterial toxin by an antitoxic noncoding RNA pseudoknot

Abstract: Bacterial small RNAs perform numerous regulatory roles, including acting as antitoxic components in toxin-antitoxin systems. In type III toxin-antitoxin systems, small processed RNAs directly antagonize their toxin protein partners, and in the systems characterized the toxin and antitoxin components together form a trimeric assembly. In the present study, we sought to define how the RNA antitoxin, ToxI, inhibits its potentially lethal protein partner, ToxN. We show through cross-inhibition experiments with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
98
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 51 publications
4
98
0
Order By: Relevance
“…Our 5= RACE experiments showed that the cleavage site was located within the repeat between adenine 26 and adenine 27 in an adenine-rich region (A/AAA), one nucleotide away from a predicted in silico ABIQantiQ cleavage site (/AAAA) (43). Interestingly, the toxin of the two other type III TA systems also cleaved RNA fragments in adenine-rich regions (ToxIN Pa , AA/AU; ToxIN Bt , A/AAAA) (32). In antiQ, this polyadenine sequence is found in the complete repeats (R1 and R2) and also in the last 0.8 repeat (R3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our 5= RACE experiments showed that the cleavage site was located within the repeat between adenine 26 and adenine 27 in an adenine-rich region (A/AAA), one nucleotide away from a predicted in silico ABIQantiQ cleavage site (/AAAA) (43). Interestingly, the toxin of the two other type III TA systems also cleaved RNA fragments in adenine-rich regions (ToxIN Pa , AA/AU; ToxIN Bt , A/AAAA) (32). In antiQ, this polyadenine sequence is found in the complete repeats (R1 and R2) and also in the last 0.8 repeat (R3).…”
Section: Discussionmentioning
confidence: 99%
“…However, when the protein (ToxN) is expressed in trans, only 1.5 repeats are necessary (25). Presumably, the key would be to have at least one complete mature repeat fragment (from cleavage site to cleavage site), with this fragment playing a critical role in toxin regulation within the type III TA systems (28,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In type III TA systems, the antitoxin molecule forms a pseudoknot structure of three antitoxin repetitions bound to three toxin molecules, leading to a hetero-hexamer triangular structure (55,56). It has also been demonstrated that the free toxin can cleave, through its endoribonuclease activity, the cognate antitoxins (36,54) as well as housekeeping bacterial RNA molecules (55,56), leading to cell death. During the phage infection process, this TA interaction is likely disrupted, leading to cell death and abortion of the phage infection.…”
Section: Discussionmentioning
confidence: 99%